Prediction of Thermophysical Properties of Methane Based on Molecular Dynamics Simulations - Zhang, Zhi; Liu, Chao; Li, Qi-Bin (Asian Journal of Chemistry, 2012)
A method based on molecular dynamics simulation with empirical correlations is proposed to predict supercritical thermophysical properties (dynamic viscosity and thermal conductivity) of methane, which experiments are difficult to test on it. This approach to obtain density resembles experiments by molecular interactions which is differ from numerical analysis of equation of state. In our modeling, the average absolute deviation is 3.8, 6.1 and 5.2 % of density, dynamic viscosity and thermal conductivity, respectively at 10 MPa with temperature changing from 160-350 K. The density results matched perfect while simulated results of dynamic viscosity and thermal conductivity in average absolute deviation increased about 2 % under the condition of simulated supercritical state. It is found that the deviations are mostly attributing to empirical correlations. This attractive issue will be discussed further in future.